Outsourcing, foreign direct investment and tourism demand - Leitão, Nuno Carlos (2018)
This text was developed based on three chapters, namely: fragmentation and outsourcing, in the second chapter we emphasize foreign direct investment and the gravity model and finally the demand for tourism. Throughout the three chapters are used explanatory models that test underlying theoretical hypotheses using econometric models (panel data and time series). The book that is published is a result of the research of the last years.